Low back pain prevalence across African populations from 2017 to 2025: a systematic review and meta-analysis - Loveness A. Nkhata; Dominique Leibbrandt; Dominic Fisher; Chinonso Igwesi-Chidobe; Linzette D. Morris; Quinette A. Louw (Frontiers in Public Health, 2026)
Background Occupational low back pain (LBP) represents a major and under-characterized health burden among African workers. While pan-continental LBP prevalence data exist for the general population, occupationally stratified meta-analytic estimates have never been produced for the full African continent. Evidence from Africa remains fragmented, with no existing review integrating occupational, general population, and pregnancy-related LBP within a single pan-continental synthesis. This systematic review and meta-analysis aimed to generate the first occupationally stratified pooled prevalence estimates of LBP across African populations and to update continental prevalence figures from studies published between 2017 and 2025. Methods A systematic review and meta-analysis was conducted following PRISMA 2020 guidelines. Seven bibliographic databases and two regional indexes (nine information sources in total) were searched for studies published between May 2017 and August 2025. Eligible studies reported point, 12-month, or lifetime LBP prevalence in African populations. Methodological quality was assessed using a validated 10-item appraisal tool. Random-effects meta-analyses used restricted maximum likelihood (REML) estimation with Hartung–Knapp adjustment to provide conservative 95% confidence intervals. Certainty of evidence was assessed using the GRADE approach. Results Twenty-six studies from fifteen African countries involving 14,339 participants were included (sample size was reported in 25 of the 26 studies). Overall pooled prevalence estimates were 53% (95% CI 40–65%; k = 8 studies) for point prevalence, 75% (95% CI 65–84%; k = 5 studies) for annual prevalence, and 65% (95% CI 54–76%; k = 13 studies) for lifetime prevalence, with substantial heterogeneity across studies. Occupational subgroup analyses showed consistently high prevalence among healthcare workers (80%, 95% CI 79–82%, I2 = 0%; k = 6 studies). Transportation workers demonstrated annual prevalence exceeding 85%, and teachers and manufacturing workers showed pooled prevalence above 70%. Pregnancy-related LBP prevalence ranged from 46 to 75% across included studies. Certainty of evidence ranged from low to moderate, mainly due to heterogeneity and imprecision. Conclusions Low back pain represents a substantial and unevenly distributed health burden across African populations, with particularly high prevalence in occupational groups exposed to physical workload. These findings highlight the need for strengthened surveillance, workplace prevention strategies, and integration of musculoskeletal care into primary and occupational health services in African settings.